Four Searches: Antoine Predock Architect - Eileen Devereux (Oz, 1988)
The power of the narrative metaphor in describing architecture and the design process is compelling and seductive. Its strength lies in a capacity to absorb and reveal concepts which elude common understanding; its weakness, in the temptation for specious interpretation where discerning analysis is required to define the distinctive elements of the architectural and linguistic systems...